Procedures in multilateral trade negotiations within the GATT/WTO international trade system - Marković Ivan (Međunarodni Problemi, 2006)
In the first part of the paper the author deals with some general aspects of the very complex process of trade negotiations. He explains that trade negotiations, bilateral or multilateral, are the basis for establishment of the international trade regime. In order to understand multilateral trade negotiations one should be familiar with its basis, which is composed of rules and procedures. Also, it is necessary to take into consideration the fact that these rules and procedures have not emerged at once but have been introduced in the process of adjustment to the needs of negotiators. In the second part of the paper the author considers the procedures in multilateral trade negotiations within the GATT/WTO international trade system.